2017
DOI: 10.1074/jbc.m116.764340
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic Snapshots of Class A β-Lactamase Catalysis Reveal Structural Changes That Facilitate β-Lactam Hydrolysis

Abstract: β-Lactamases confer resistance to β-lactam-based antibiotics. There is great interest in understanding their mechanisms to enable the development of β-lactamase-specific inhibitors. The mechanism of class A β-lactamases has been studied extensively, revealing Lys-73 and Glu-166 as general bases that assist the catalytic residue Ser-70. However, the specific roles of these two residues within the catalytic cycle remain not fully understood. To help resolve this, we first identified an E166H mutant that is funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 47 publications
3
24
0
Order By: Relevance
“…Overall, our structures reveal that Ser70 is primed by deprotonation for nucleophilic attack on the AVI C-7 atom. It is still uncertain if this deprotonation is driven by Lys73 or Glu166 via a catalytic water that bridges both Glu166 and Ser70 (17)(18)(19)(20)(21)(22). Using both highresolution structural studies and molecular dynamics simulations, both Lys73 and Ser130 are also believed to participate in a proton shuttle resulting in the protonation of the AVI N-6 in the acylation step (15,23).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, our structures reveal that Ser70 is primed by deprotonation for nucleophilic attack on the AVI C-7 atom. It is still uncertain if this deprotonation is driven by Lys73 or Glu166 via a catalytic water that bridges both Glu166 and Ser70 (17)(18)(19)(20)(21)(22). Using both highresolution structural studies and molecular dynamics simulations, both Lys73 and Ser130 are also believed to participate in a proton shuttle resulting in the protonation of the AVI N-6 in the acylation step (15,23).…”
Section: Resultsmentioning
confidence: 99%
“…As has been suggested before (e.g. (56,58,59)), the Lys73 sidechain may need to be in one conformation for efficient substrate binding and another for efficient product release. Thus, it seems possible that the two conformations observed in crystal structures of Toho-1 ( [57][58][59][60] and BlaC, (53) are the cause of the two forms that we observe in the NMR spectra of the BlaCclavulanic acid adduct.…”
Section: Downloaded Frommentioning
confidence: 94%
“…PenP is a class A ␤-lactamase from Bacillus licheniformis with over 80% sequence similarity to the clinically significant TEM-1. Our previous studies have also confirmed that the kinetic profile of PenP is nearly identical to that for TEM-1, showing a narrow substrate profile with more effective hydrolysis of only first-and second-generation penicillins and cephalosporins (19,20). P99, on the other hand, is an AmpC ␤-lactamase (also termed class C ␤-lactamase) from Enterobacter cloacae.…”
Section: Resultsmentioning
confidence: 63%